Hydrogenolysis of Glycerol to 1,2-Propanediol Over Clay Based Catalysts - Lee, Sang-Yong; Jung, Jae-Sun; Yang, Eun-Hyeok; Lee, Kwan-Young; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2015)
1,2-propanediol (1,2-PDO) is one of the promising product among the valuable products derived from glycerol and it can be obtained by the catalytic hydrogenolysis of glycerol. Copper-supported clay-based catalysts were prepared with different pore sizes using various ratios of kaolin, Mg, and Al by coprecipitation and applied in the selective hydrogenolysis of glycerol to 1,2-PDO. In recent research, variations of pore volume and pore size could affect the diffusion of reagents within the catalyst due to the collision between reagents or pore wall and reagents. It changes selectivities of each product in hydrogenolysis of glycerol reaction. The physico-chemical properties of the catalysts were analyzed by XRD, N-2 physisorption, TPR, CO2-TPD, SEM, and a mercury porosimeter. The Cu/TALCITE 4 catalyst showed 98% 1,2-PDO selectivity with 65% glycerol conversion under the optimized condition of 190 degrees C, 25 bar, and 20 wt% glycerol aqueous solution. It was found that the basic strength and meso-macro pore structure of the catalysts play an important role in glycerol conversion and 1,2-PDO selectivity.
Keywords: PRECIPITATION-GEL METHOD; PROPYLENE-GLYCOL; CONVERSION